L’invisibilisation des femmes dans les recherches sur la prison - Corinne Rostaing (Les Cahiers de Framespa)
The aim of this article is to question the implicit brakes in the knowledge of the women prisons. How can we explain the low number of scientific productions on the women in prison ? Do the low number of imprisoned women – who represent less than 4 % of the prison population – justify their reduced part in the productions of social sciences ? The explanation « too few to count » is not sufficient. Most of the studies on prisons refer to « prisoners », without more precision, and they generally concern only men. This article, based on reflexive returns on experiences of research in French prisons, attempts to describe the processes by which the women become invisible in the scientific field. We shall clear some types of processes, such as the non-distinction of prisoners, such as androcentrism or such as the valuation of the specificity of the prisoners. Each of these processes will be discussed, with their principle of justification and their effects.